Sclerosing peritonitis associated with luteinized thecoma and elevated serum CA 125 levels: case report - Vieira, Sabas Carlos; Santos, Lina Gomes dos; Cruz, Felipe José da Silva Melo; Gonçalves, Wildson Moura; Rocha, Sheila de Farias Viana Castelo Branco (São Paulo Medical Journal, 2008)
CONTEXT: Thecomas are benign tumors that account for less than 1% of all ovarian neoplasms. The association of ovarian thecoma with sclerosing peritonitis is rare. CASE REPORT: We report the case of a 33-yearold woman, with a two-month history of increasing abdominal volume. Ultrasound showed a complex pelvic lesion and laboratory analysis detected elevated serum CA 125 levels. The patient underwent total abdominal hysterectomy with bilateral salpingo-oophorectomy and peritoneal biopsy. Histopathological analysis revealed the presence of luteinized thecoma of both ovaries associated with sclerosing peritonitis.